Private land, public benefits: Conservation covenants and easements aiding global biodiversity targets - Benjamin J. Richardson; Sarah Brugler; Phillipa C. McCormack; James A. Fitzsimons (Land Use Policy, 2027)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Upscaling marine and coastal restoration through legal and governance solutions: Lessons from global bright spots - Justine Bell-James; Nicole Shumway; Jaramar Villarreal-Rosas; Dominic A. Andradi-Brown; Christopher J. Brown; James A. Fitzsimons; Rose Foster; Evan Hamman; Catherine E. Lovelock; Megan I. Saunders; Nathan J. Waltham (Environmental Science & Policy, 2025)

Sedimentary ancient DNA reveals the impact of anthropogenic land use disturbance and ecological shifts on fish community structure in small lowland lake - Georgia Thomson-Laing; Jamie D. Howarth; Javier Atalah; Marcus J. Vandergoes; Xun Li; John K. Pearman; Sean Fitzsimons; Chris Moy; Adelaine Moody; Claire Shepherd; Nicholas McKay; Susanna A. Wood (Science of The Total Environment, 2024)

Turning a lost reef ecosystem into a national restoration program - Dominic McAfee; Ian M. McLeod; Heidi K. Alleway; Melanie J. Bishop; Simon Branigan; Sean D. Connell; Craig Copeland; Christine M. Crawford; Ben K. Diggles; James A. Fitzsimons; Ben L. Gilby; Paul Hamer; et al. (Conservation Biology, 2022)
Achieving a sustainable socioecological future now requires large‐scale environmental repair across legislative borders. Yet, enabling large‐scale conservation is complicated by policy‐making processes that are disconnected from socioeconomic interests, multiple sources of knowledge, and differing applications of policy. We considered how a multidisciplinary approach to marine habitat restoration generated the scientific evidence base, community support, and funding needed to begin the restoration of a forgotten, functionally extinct shellfish reef ecosystem. The key actors came together as a multidisciplinary community of researchers, conservation practitioners, recreational fisher communities, and government bodies that collaborated across sectors to rediscover Australia's lost shellfish reefs and communicate the value of its restoration. Actions undertaken to build a case for large‐scale marine restoration included synthesizing current knowledge on Australian shellfish reefs and their historical decline, using this history to tell a compelling story to spark public and political interest, integrating restoration into government policy, and rallying local support through community engagement. Clearly articulating the social, economic, and environmental business case for restoration led to state and national funding for reef restoration to meet diverse sustainability goals (e.g., enhanced biodiversity and fisheries productivity) and socioeconomic goals (e.g., job creation and recreational opportunities). A key lesson learned was the importance of aligning project goals with public and industry interests so that projects could address multiple political obligations. This process culminated in Australia's largest marine restoration initiative and shows that solutions for large‐scale ecosystem repair can rapidly occur when socially valued science acts on political opportunities.

Lake microbial communities are not resistant or resilient to repeated large‐scale natural pulse disturbances - Katie A. Brasell; Jamie Howarth; John K. Pearman; Sean J. Fitzsimons; Anastasija Zaiko; Xavier Pochon; Marcus J. Vandergoes; Kevin S. Simon; Susanna A. Wood (Molecular Ecology, 2021)
Opportunities to study community‐level responses to extreme natural pulse disturbances in unaltered ecosystems are rare. Lake sediment records that span thousands of years can contain well‐resolved sediment pulses, triggered by earthquakes. These palaeorecords provide a means to study repeated pulse disturbances and processes of resistance (insensitivity to disturbance) and ecological resilience (capacity to regain structure, function and process). In this study, sedimentary DNA was extracted from a sediment core from Lake Paringa (New Zealand) that is situated in a near natural catchment. Metabarcoding and inferred functions were used to assess the lake microbial community over the past 1100 years – a period that included four major earthquakes. Microbial community composition and function differed significantly between highly perturbed (postseismic, ~50 years) phases directly after the earthquakes and more stable (interseismic, ~250 years) phases, indicating a lack of community resistance. Although community structure differed significantly in successive postseismic phases, function did not, suggesting potential functional redundancy. Significant differences in composition and function in successive interseismic phases demonstrate that communities are not resilient to large‐scale natural pulse disturbances. The clear difference in structure and function, and high number of indicator taxa (responsible for driving differences in communities between phases) in the fourth interseismic phase probably represents a regime shift, possibly due to the two‐fold increase in sediment and terrestrial biospheric organic carbon fluxes recorded following the fourth earthquake. Large pulse disturbances that enhance sediment inputs into lake systems may produce an underappreciated mechanism that destabilises lake ecosystem processes.

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Factors influencing property selection for conservation revolving funds - Mathew J. Hardy; James A. Fitzsimons; Sarah A. Bekessy; Ascelin Gordon (Conservation Biology, 2018)
Finding sustainable ways to increase the amount of private land protected for biodiversity is challenging for many conservation organizations. In some countries, organizations use revolving‐fund programs, whereby land is purchased and then sold to conservation‐minded owners under condition they enter into a conservation covenant or easement. The sale proceeds are used to purchase, protect, and sell additional properties, incrementally increasing the amount of protected private land. Because the effectiveness of this approach relies on selecting appropriate properties, we explored factors currently considered by practitioners and how these are integrated into decision making. We conducted exploratory, semistructured interviews with managers from each of the 5 major revolving funds in Australia. Responses indicated although conservation factors are important, financial and social factors are also highly influential. A major determinant was whether the property could be resold within a reasonable period at a price that replenishes the fund. To facilitate resale, often selected properties include the potential for the construction of a dwelling. Practitioners face with clear trade‐offs between conservation, financial, amenity, and other factors in selecting properties and 3 main challenges: recovering the costs of acquisition, protection, and resale; reselling the property; and meeting conservation goals. Our findings suggest the complexity of these decisions may constrain revolving‐fund effectiveness. Drawing from participant responses, we identified potential strategies to mitigate these risks, such as providing adequate recreational space without jeopardizing ecological assets. We suggest managers could benefit from a shared‐learning and adaptive approach to property selection given the commonalities between programs. Understanding how practitioners deal with complex decisions in the implementation of revolving funds helps identify future research to improve the performance of this conservation tool.

A hydroclimate-proxy model based on sedimentary facies in an annually laminated sequence from Lake Ohau, South Island, New Zealand - Heidi A. Roop; Richard Levy; Gavin B. Dunbar; Marcus J. Vandergoes; Jamie Howarth; Sean Fitzsimons; Heung Soo Moon; Christian Zammit; Robert Ditchburn; Troy Baisden; Ho Il Yoon (Journal of Paleolimnology, 2016)

All‐sky radiation over a glacier surface in the Southern Alps of New Zealand: characterizing cloud effects on incoming shortwave, longwave and net radiation - J. P. Conway; N. J. Cullen; R. A. Spronken‐Smith; S. J. Fitzsimons (International Journal of Climatology, 2015)
Clouds are important features of many high‐altitude and glaciated areas, yet detecting their presence and specifying their effects on incoming shortwave ( SW ↓), longwave ( LW ↓) and net all‐wave radiation ( Rnet ) remains challenging in these environments. These limitations hamper efforts to understand atmospheric controls on glacier surface mass balance ( SMB ) in the Southern Alps of New Zealand, as both cloud and airmass forcing accompanies key synoptic controls on SMB . Multi‐year datasets of four‐component broadband radiation from two sites at Brewster Glacier, Southern Alps of New Zealand, are used here to develop cloud metrics to account for the effects of clouds on SW ↓, LW ↓ and Rnet . On average 23% of top‐of‐atmosphere shortwave radiation (SW TOA ) is attenuated by the clear‐sky atmosphere, while clouds attenuate a further 31%, resulting in TOA being received at the surface. The transmission of shortwave radiation by clouds ( trc ) during overcast conditions is found to vary with season and airmass characteristics. A simple parameterization is developed to account for lower trc observed during periods of higher water vapour pressure. Cloud metrics derived at the site show overcast conditions are frequent (45% of period) and strongly dependent on wind direction, highlighting the dominant role of orography in cloud formation and enhancement in the Southern Alps. The effect of clouds on Rnet exhibits a distinct seasonal variation; during summer when albedo and trc are lower, clouds decrease Rnet by 20–40 W m −2 , while during autumn, winter and spring, clouds enhance Rnet by approximately 20 W m −2 . Idealized modelling shows that these patterns are strongly dependent on albedo and extend across the elevation range of glaciers in the Southern Alps. Thus, overcast conditions appear to aid the extension of ablation into spring and autumn by increasing the energy available for snow and ice melt.

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Development of an Insulated Reporter System to Search for Cis-Acting DNA Sequences Required for Dosage Compensation in Drosophila - Helen L. Fitzsimons; Rebecca A. Henry; Maxwell J. Scott (Genetica, 2000)

Development of an insulated reporter system to search for cis-acting DNA sequences required for dosage compensation in Drosophila - Helen L. Fitzsimons; Rebecca A. Henry; Maxwell J. Scott (Genetica, 1999)